Deformation characteristics of polypropylene thread (p-1) for synthetic slings (Международный научный журнал «Инженер», 2026)
The article presents the deformation characteristics of polymeric materials, in particular, synthetic threads for lifting slings, which are used in rigging. Influence of temperature on the characteristics of deformation and strength properties of synthetic fibers. Relationships between the characteristics of deformation properties and molecular processes occurring in polyolefin threads are revealed. The characteristics of multifilament threads, from which synthetic slings are made, as well as deformation and mechanical characteristics, are given.